Pengaruh CAR, BOPO, dan NPM Terhadap Retrun On Assets (ROA) pada Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia - Nurmala Nurmala; Dian Ayu Andriani (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study examines the influence of Capital Adequacy Ratio (CAR), Operating Expenses to Operating Income (BOPO), and Net Profit Margin (NPM) on Return on Assets (ROA) in banking companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The main issue addressed is the inconsistency between theoretical expectations and empirical conditions observed in the banking sector, where fluctuations in financial ratios do not always align with changes in profitability. This research aims to analyze both the simultaneous and partial effects of CAR, BOPO, and NPM on ROA. A quantitative approach was applied using secondary data obtained from published financial statements. The sample consists of 26 banks, resulting in 78 observations. Data were analyzed using multiple linear regression with classical assumption tests. The results indicate that, simultaneously, CAR, BOPO, and NPM significantly affect ROA. Partially, CAR and BOPO show no significant effect on ROA, while NPM has a positive and significant effect on ROA. The coefficient of determination (R²) shows that 36% of ROA variation can be explained by the independent variables, while the remaining 64% is influenced by other factors outside the model.